Online generic diagnostic reservoir operation tools. (January 2021) - Zhao, Qiankun; Li, Donghui; Cai, Ximing
Abstract: The actual use of models and decision tools for real-world reservoir operations is limited due to the gap between the models/tools and the real-world practices, tedious amount of work in case-by-case model developments, and computational difficulty of running complex numerical models. This paper presents generic diagnostic reservoir operation tools (DROT). The tools are developed based on generic properties derived from analytical optimization studies and data mining procedures. Instead of establishing a numerical model, DROT users can apply particular properties and/or procedures to diagnose a specific reservoir operation problem by just providing required inputs. DROT is available online and also provides auxiliary tools such as a data retrieval tool and a data visualization tool. DROT provides an open software framework that can include additional generic tools of models, algorithms, and functions. DROT can be used by reservoir operators, researchers, and students to obtain diagnostic information for the operation of a reservoir. Highlights: Analytical studies on reservoir operation are implemented as generic online tools. A data mining algorithm is realized for revealing real-world operations. Auxiliary tools for data retrieval and data visualization are developed with DROT. DROT provides diagnostic information for reservoir operations. DROT presents a software framework to include additional generic tools.